Pentingnya Implementasi Iso Pada Perguruan Tinggi : Sistematik Literature Review - Syndi Nurina Widyaningrum (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2019)
The use of information technology has entered all aspects of the world. Especially in the field of Education. The banking industry has undergone major changes in recent years coupled with the development of information technology used by universities to gain competitive advantage. ISO 9001 is an international standard for quality management systems (QMS). The standard was first published in 1987 and was revised in 1994, 2000 and 2008. One of the quality management system (SMM) standards that has been developed is ISO 9001. ISO 9001 version 2000 and 2008 version prioritizes the pattern of business processes that occur within company organizations. This study uses the Systematic Literature Review Method by using Library Studies in the form of Articles in obtained from Google Schoolar, Science Direct, and Sinta Dikti. The purpose of this study was to find out the most ISO standards used in universities. In the Journal, which is made as Literature Review, it turns out that in many universities, it implements ISO 9001 in the field of Quality Management. The use of ISO 9001 in the field of quality management can be done in a variety of activities, especially administration and academics.